Transformable topological mechanical metamaterials - D. Zeb Rocklin (Nature Portfolio, 2017)
Here Rocklinet al. propose a design principle using operations that cost little energy and realize mechanical metamaterials that can be easily and reversibly transformed between states with different mechanical and acoustic properties.